O estatuto da cidade como instrumento do planejamento urbano nos municípios de Cuiabá e Várzea Grande - MT - Ferreira, Enodes Soares (2015)
With the change in the production process, generated by the Industrial Revolution of the nineteenth century, the relationship between country and city underwent major transformations. The population in Brazil that until the 60s was basically rural in less than 10 years has become urban and living in big cities, this phenomenon led to major changes in the landscape. Many social and spatial problems and suggest further aggravated due to the great demand as the lack of infrastructure and unemployment. To solve these problems many plans and projects were developed, more due to lack of legal grounds, almost all did not achieve the expected success. Given these numerous problems and difficulties of municipal managers get good solutions, Congress, pressured by urban planners and the Popular Fronts, after 12 years of discussion, approved in 2001 Law No. 10.257 / 2001, known as City Statute. This law creates a milestone in public policies of urban planning, and more than that, it gives managers and municipal urban planners, mechanisms with legal grounds for them to be used by urban managers in practice everyday. One of the best known instruments City Statute is the requirement for preparation of Master Plans “participatory”. The city of Cuiabá and Várzea Grande, in the year of publication of the City Statute, already had Master Plans. With the new legislation due revision was necessary. With the review and public participation in seminars and meetings the new Master Plans were approved and promulgated in 2007. Past twelve years of publication of the City Statute, the question arises, what has changed in the urban landscape of the city of Cuiabá and Várzea Great, what instruments are being used, and what are the results. The objective of this study is to determine when and where it is going to change in the urban landscape because of the City Statute. The idea of this study was to map the changes to take a broad view, a better scale, in order to subsidize the new urban public policies, every time, but participative, preparing them for future demands.